Phenolic profile and antimicrobial activity of dietary supplements based on Cochlospermum angolensis Welw - Pereira, Carla (2016)
Cochlospermum angolensis Welw. (borututu) is a widespread tree in Angola that belongs to the Cochlospermaceae family. Its bark infusion is used in the traditional medicine of Angola for the treatment of jaundice, hepatic diseases and for the prophylaxis of malaria [1]. In the present work, three formulations based on this plant (infusion, pills, and syrup) were characterized by HPLC-DAD-ESI/MS regarding phenolic composition, and evaluated by their in vitro antimicrobial activity against isolates of multiresistant bacteria (Escherichia coli, Escherichia coli spectrum extended producer of β-lactamases (ESBL), Proteus mirabilis, methicillin-resistant Staphylococcus aureus (MRSA) and Pseudomonas aeruginosa). The infusion and pills revealed the highest variety of phenolic compounds, with eleven compounds identified. Protocatechuic acid was only present in infusions, being the most abundant compound, while (epi)gallocatechin-O-gallate and eucaglobulin/globulusin were the main molecules identified in pills and syrup, respectively. Methyl ellagic acids, eucaglobulin/globulusin B (Fig. 1) and (epi)gallocatechin-O-gallate were found in all the formulations. The infusion revealed antimicrobial activity against all the studied bacteria with the exception of P. mirabilis whereas the pills revealed activity in E. coli ESBL and MRSA. No significant antimicrobial activity was detected in the syrup, in agreement with its low concentrations of phenolic compounds. None of the tested formulations inhibited P. mirabilis. Considering the obtained results, C. angolensis infusion can be considered a good source of phenolic compounds as well as a good antimicrobial agent.